Proses Rekrutmen Sumber Daya Manusia Partai Politik Pada Pileg 2014 (Studi Kasus Proses Rekrutmen Calon Anggota Legislatif Di Dpw Partai Nasdem Diy) - Analius Giawa; Tri Daya Rini (Universitas Muhammadiyah Yogyakarta, 2017)
The development of democracy values in Indonesia are strongly influenced by the presence of political parties. It is because the political parties are the instrument of democracy. A political party is being one for public facilities in developing participatory culture. NasDem party is one of new party that has joined general election in 2014 with slogan “restoration” trying to build political communication with reveal himself as “party without expense/charge”. However, to achieve the success and the purpose of NasDem party, it is necessary to do political recruitment for legislative candidates. In order to create a good organization, it would be needed a good human resources in the recruitment process, transparent, and accountable. This research tries to find out how the recuitment process of human resources to become a legislative member candidate in NasDem party. The research method used descriptive qualitative method. In the determination of informants using a combination technique between purposive and snowball. Data analysis used interactive analysis technique Miles and Huberman model. The result showed that the recruitment process of human resources do not have clear benchmark, not transparent, and elite domination in determining the outcome of a selection process. The result of the recruitment process is only become an elite domain within the party’s internal but have not been able to be the result of the decision based on deliberations as an organization.